Controlling quantum many-body dynamics in driven Rydberg atom arrays - Bluvstein, D.; Omran, A.; Levine, H.; Keesling, A.; Semeghini, G.; Ebadi, S.; Wang, T. T.; Michailidis, A. A.; Maskara, N.; Ho, W. W.; Choi, S.; Serbyn, M.; et al. (Science (American Association for the Advancement of Science), 2021)
Dynamic stabilization of an array Large-scale systems comprising one-dimensional chains and two-dimensional arrays of excited atoms held in a programmable optical lattice are a powerful platform with which to simulate emergent phenomena. Bluvsteinet al.built an array of up to 200 Rydberg atoms and subjected the system to periodic excitation. Under such driven excitation, they found that the array of atoms stabilized, freezing periodically into what looked like time crystals. Understanding and controlling the dynamic interactions in quantum many-body systems lies at the heart of contemporary condensed matter physics and the exotic phenomena that can occur. Science, this issue p.<related-article issue='6536' page='1355' related-article-type='in-this-issue' vol='371'>1355</related-article>